1991
DOI: 10.1080/02614369100390211
|View full text |Cite
|
Sign up to set email alerts
|

In the eye of the beholder: perceptions of female and male outdoor leaders

Abstract: The theory of expectation states suggests that each individual has certain performance and behavioural expectations of themselves and others in society. Those expectations are based on various roles people play within society. People in leadership roles are ascribed high status; others look up to them and grant them power and dominance. The literature also reveals that, based on gender, males are ascribed higher status than females. This can result in gender bias favouring males. This paper reports an examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…Many indicated it is critical to eradicate the view held by some that female leaders are weak, lack confidence and assertiveness; women themselves should be actively involved in solving these problems. Jordan (1991) explored this particular issue and suggested it may be overcome, in part, by providing trainee outdoor leaders with relevant information (e.g., information about expectations and reactions to incongruent situations) as well establishing strategies which ensure a better balance in male/female leaders. She suggested that participants, leaders and administrators all have a role to play in changing peoples' perceptions of male/female leaders.…”
Section: Discussionmentioning
confidence: 98%
“…Many indicated it is critical to eradicate the view held by some that female leaders are weak, lack confidence and assertiveness; women themselves should be actively involved in solving these problems. Jordan (1991) explored this particular issue and suggested it may be overcome, in part, by providing trainee outdoor leaders with relevant information (e.g., information about expectations and reactions to incongruent situations) as well establishing strategies which ensure a better balance in male/female leaders. She suggested that participants, leaders and administrators all have a role to play in changing peoples' perceptions of male/female leaders.…”
Section: Discussionmentioning
confidence: 98%
“…Because the 'manliness' ideology was integrated into the foundational strategies of camp leadership, people for whom camp has played an important role may have unconsciously internalized the idea that masculine and patriarchal qualities are the correct, or most effective, qualities for leadership, even when (or perhaps because) camps promote a home-like (gendered) environment. As Jordan (1991) argues, 'a pro-male bias tends to be greatest when the task at hand is incongruent with gender role expectations for women ' (p.242).…”
Section: Discussionmentioning
confidence: 99%
“…The emergent analysis of women in outdoor recreation leadership has opened up questions about women in sport, women in the outdoors, and women in high-risk or adventure challenge programs (see Johnson, 1990; Jordan, 1991; Garvey and Gass, 1999; Clemmensen, 2002; Saunders and Sharp, 2002; Sharpe, 2005; Warren, 2006; Rilling and Jordan, 2007). These studies find that attitudinal gender discrepancies toward leaders also exist in the field of outdoor recreation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As individuals are motivated to work in the outdoor recreation field, a gender disparity between male and females exists. Outdoor recreation is considered to be a male dominated field and as a result researchers have studied gender role incongruence within the field of outdoor leadership (Carter & Colyer, 1999;Jordan, 1991;Warren & Loeffler, 2007;Wittmer, 2001). With an increase in the numbers of female outdoor activity participation, these authors suggest employing more women in the field of outdoor recreation so as to give women in leisure role models to emulate.…”
Section: Employment In Outdoor Recreationmentioning
confidence: 99%